Changes in students' conceptions of chemical equilibrium using card game simulations - Cabrestante, Jenelyn P. (Animo Repository, 2004)
This study on conceptual change teaching explored students pre- intervention and post-intervention understanding of chemical equilibrium. It took a closer look on how students perceive the concept of chemical equilibrium, the reversible and dynamic nature of chemical equilibrium, the concept of equilibrium constant, and the factors affecting chemical equilibrium. In addition, it explored the level of students understanding of the abovementioned concepts. Furthermore, it revealed the types of conceptual change occurring among students, and it scrutinized the role played by analogy in fostering conceptual change. The study was presented through the Modified Teaching- With- Analogy (MTWA)- based card game simulations. This endeavor involved one intact chemistry class at the Palawan State University during the school year 2003-2004. The respondents were composed of twenty BS in Marine Biology freshmen taking up Chem18/Lab. The research design used was qualitative, where data were gathered using the following: card game simulated activities, 13-item Conceptual Understanding Test with open-ended portion, post-intervention unstructured interview, students journal, worksheets, and classroom observations. Data obtained were subjected to phenomenographic analysis in order to categorize students conceptions. Conceptual trace analysis was done to give a thorough description of the level of their understanding as well as the type of conceptual change undertaken by students. Results were presented in descriptive-interpretive form. Prior to the intervention, majority of students conceptions were in the level of worst understanding (WU). The same level of understanding prevailed after the intervention. However, there was a decrease in the percentage of conceptions falling within this level, and there was an increase in levels such as, correct/ incomplete (CI) and partial understanding (PU). CI level is characterized by incomplete knowledge with minor misconception, while PU level is characterize